Abundance and taxonomic data of carabids collected with pitfall traps from temperate forest stands from Lower Saxony, Germany in 2019 - Matevski, Dragan; Kriegel, Peter (In: Matevski, D; Kriegel, P (2022): Abundance and taxonomic data of arthropods collected with pitfall traps from temperate forest stands from Lower Saxony, Germany in 2019 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.949484, 2022)
Abundance and taxonomic data of carabids collected with pitfall traps from temperate forest stands from Lower Saxony, Germany. Five forest stand types were studied (Douglas fir monoculture, European beech/Douglas fir mixture, European beech monoculture, European beech/Norway spruce mixture, Norway spruce monoculture) at eight different sites, four in southern (site 1-4) and three (5-8) in northern Lower Saxony, Germany. Twelve pitfall traps were set at each of the 40 plots and the material was collected every three weeks starting from 03.09.2019.
Keywords: Beech forest; Carabidae; Douglas fir; European beech; Lower Saxony; Norway spruce; RTG2300; temperate forests